2004
DOI: 10.1111/j.1365-2249.2005.02695.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Th1 cells and heat shock protein 60 in the pathogenesis of intestinal Behçet's disease

Abstract: Summary Involvement of excessive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 37 publications
2
87
1
1
Order By: Relevance
“…We have also observed heavy infiltration of CD4 + and CD8 + T cells into the intestinal lesions of BD patients, and have detected the expression of mRNAs for proinflammatory and Th1 cytokines/chemokines 12) . Kobayashi et al observed the accumulation of lymphocytes around the vasa vasorum in six patients with vascular BD, as well as expression of proinflammatory cytokines by these cells, including IL-1 alpha, TNF-alpha, and IFN-gamma 13) .…”
Section: Th1 Cell Dominance In Bdmentioning
confidence: 91%
“…We have also observed heavy infiltration of CD4 + and CD8 + T cells into the intestinal lesions of BD patients, and have detected the expression of mRNAs for proinflammatory and Th1 cytokines/chemokines 12) . Kobayashi et al observed the accumulation of lymphocytes around the vasa vasorum in six patients with vascular BD, as well as expression of proinflammatory cytokines by these cells, including IL-1 alpha, TNF-alpha, and IFN-gamma 13) .…”
Section: Th1 Cell Dominance In Bdmentioning
confidence: 91%
“…Histopathological studies also point to a Th1 type tissue infiltration in ABD, possibly driven by the highly expressed IL-12 and IL-23 in intestinal and cutaneous lesions. Interestingly, both streptococcal antigens and auto-antigens, such as aB-crystallin also drive an IL-12 mediated response in ABD (Imamura et al, 2005;Kulaber et al, 2007;Lew et al, 2008;Yanagihori et al, 2006). Concerning Th2 type of immune response, both, cells and signature cytokines, such as IL-4, IL-10 and IL-13 are reported to be unaffected or decreased in ABD by most researchers in the serum or in the aqueous humor.…”
Section: T Cell Abnormalitiesmentioning
confidence: 99%
“…Functional abnormalities of these receptors or different activation cascades by different microorganisms are associated with disease pathogenesis in BD [73]. Human HSP60 induces a potent inflammatory response in the innate immune system via its ligands, TLRs, and operates in a similar manner to that of classical pathogen-derived ligands and can thus activate nonspecifically the innate immune system and stimulates the maturation of dendritic cells [6]. In some studies, the expression of TLR1, TLR2, TLR4, and TLR6 on monocytes and granulocytes in patients with BD was investigated, which showed increased expression of TLR4, but not TLR2 and others, by peripheral blood mononuclear cells [73,74].…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
“…Today, BD is considered a more complicated entity [2] and is defined as a chronic, relapsing, multisystemic idiopathic inflammatory problem with mucocutaneous (erythema nodosum, pustular vasculitis), ocular (anterior and posterior uveitis), arthritic, vascular (both arterial and venous vasculitis), and central nervous system (meningoencephalitis) involvements [3][4][5]. The etiology and pathogenesis of this disease have been explored extensively [6]; genetic susceptibility, environmental factors (viral and/or bacterial infections), inflammatory response abnormalities (heat shock proteins (HSPs), dysregulated nitric oxide production) and abnormal immune responses play a major role in BD pathogeny [7]. Current evidence lends increasing support to immunoinflammatory mechanisms as one of the prime pathogenic processes involved in the development and progression of BD [8].…”
mentioning
confidence: 99%